Gastroprotective activity of semi-purified (partitions) Methanolic leaf extract of melastoma malabathricum l. (senduduk - Ismail Suhaimy, Noor Wahida (2016)
Melastoma malabathricum L. (Melastomaceae) is traditionally used by the Malays to treat gastric ulcer and this claim was supported by the gastroprotective activity observed with methanolic extract of M. malabtahricum leaves (MEMM). The present study aimed to determine the gastroprotective activity of the methanolic crude extract of Melastoma malabathricum (MEMM) by semi-purified extract (partitions) using solvents of different polarities. The study began with screening the potential acute toxicity of MEMM before it was partitioned using different solvents. The petroleum ether partition (PEMM) was non-polar, ethyl acetate partition (EAMM) was intermediate polar and aqueous extract (AQMM) was polar. Next, we screened their phytochemical compounds followed by evaluation of their in vitro antioxidant activities using total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH), superoxide dismutase (SOD) and oxygen radical absorbance capacity (ORAC) assays and screened their in vitro anti-inflammatory activities using xanthine oxidase (XO) and lipoxygenase (LOX) assays. All partitions were investigated for possible gastroprotective activity against ethanol-induced gastric ulcer. Rats (n = 6) received 10% dimethyl sulfoxide (DMSO, negative control), 100 mg ranitidine (positive control) or semi-purified extract (50, 250, 500 mg/kg) orally once daily for 7 days followed by ulcer induction using absolute ethanol (1 mL/200 gm). The gastric tissues were collected for macroscopic and microscopic examination to determine the most effective partition. The most effective partition was selected for studied their antisecretory activity by using a pylorus ligation model to determine the gastric juice volume, pH, free and total acidity, and mucus content. The selected partition progressed to the next stage of the study, to determine the antioxidant enzyme activity (SOD, catalase [CAT], glutathione [GSH], thiobarbituric acid–reactive substances [TBARS]) and cytoprotective activity (prostaglandin E2 [PGE2]) in gastric tissues. The effective dose of the partition was investigated to determine the possible involvement of endogenous nitric oxide (NO) and sulfhydryl (SH) compounds in the gastroprotective effects. Finally, the compounds responsible for gastroprotection in the effective partition were identified. Result showed phytochemical screening of PEMM, EAMM and AQMM revealed the presence of saponins, flavonoids, triterpenes, tannins and polyphenolic, but not alkaloids. In the in vitro antioxidant assay, i) EAMM showed high TPC content compared to PEMM and AQMM, ii) all partitions showed high scavenging activity in the SOD assay; EAMM and AQMM showed better results as compared to PEMM in the iii) DPPH and iv) ORAC assays. In the in vitro antiinflammatory assay, the partitions had low activity in the XO assay while EAMM and AQMM had moderate and low activity, respectively, in the LOX assay. All partitions exerted significant (p < 0.05) gastroprotection against ethanol-induced gastric ulcer in the following order: EAMM > AQMM > PEMM. EAMM was the most effective partition as proven via its mechanisms of action: i) anti-secretory activity as shown by the reduction of gastric juice volume, free and total acidity as well as increased pH and gastric wall mucus, ii) antioxidant enzyme activity as shown by the increased SOD, CAT, GSH and decreased malondialdehyde (MDA) in gastric tissues, iii) cytoprotective activity as shown by the increased PGE2 levels in gastric tissue. The gastroprotective activity involved NO and SH compounds, as shown by the partition being ineffective in iv) assay when N-omega-nitro-L-arginine methyl ester (L-NAME; a NO blocker) and v) N-ethylmaleimide (NEM; a SH blocker) were used. In conclusion, EAMM showed better in vitro antioxidant and antiinflammatory activity partly attributed to its gastroprotective activity demonstrated via the mechanisms of action of its anti-secretory, antioxidant and cytoprotective activity that depend on the presence of NO and SH. The presence of flavonoids-based compounds and hydrocinnamic acid compounds which might act synergistically was believed to contribute to this gastroprotective activity.